Muscle morphological adaptations to resistance training and sports participation in children and adolescents: a scoping review - Enomoto, Shota; Tottori, Nobuaki (Frontiers in Sports and Active Living, 2025)
IntroductionThis scoping review aimed to systematically map the existing literature on the effects of resistance training (RT) and sports participation on muscle morphology in children and adolescents.MethodsHerein, a literature search was conducted using three electronic databases: PubMed, Scopus, and Web of Science. The inclusion criteria were as follows: articles that were written in English, which used chronic RT or a combination of RT with other training methods, or investigated the effects of sports participation, and reported muscle morphology as an outcome.ResultsThis scoping review included 29 studies: 17 cross-sectional studies, 3 prospective observational studies, and 9 interventional studies. The following distribution was obtained after categorizing the included studies according to participant age: aged 6–11 years, 12 articles; aged 12–14 years, 10 articles; and aged 15–17 years, 10 articles. The designs of interventional studies included eight quasi-experimental parallel-group trials and a quasi-experimental crossover trial. However, none of the included interventional studies followed the CONSORT guidelines for conducting randomized controlled trials. Across the included studies, 14 different sports were analyzed for their effects on muscle morphology. Four studies combined players from various sports. In the included studies, 47 different muscles or muscle groups were examined. Our results identified unexplored muscles because our included studies did not examine the volume of lower leg muscles.ConclusionFuture research directions in this field, including experimental design and targeted muscles, are warranted.